Alternative Dispute Resolution (ADR) Hybrid in Cameroon as a Form of Legal Protection for Consumers of Defective Products - Amandong, Egute Matthew (Faculty of Law, Universitas Brawijaya, 2021)
As part of the awareness creation exercise, this paper seeks to establish that consumers of defective products in Cameroon should be exposed to the various extra-judicial channels once they can be adopted by Government and through which the consumers can enforce their rights. This is known as Alternative Dispute Resolution (ADR). The acronym ADR is a group of flexible approaches which could be applied in resolving disputes related to defective products more quickly and at a lower cost than going through the tedious road of adversarial proceedings. ADR mechanisms generally are intended to mean alternatives to the traditional court process. Their adoption will involve the use of impartial interveners who are referred to as â€œthird partiesâ€ or â€œneutralsâ€. On the whole, the choice of a consumer redress mechanism is a choice between judicial and non-judicial mechanisms. The paper argues that, considering the difficulties encountered by the consumer within the adversarial system, the non-judicial mechanisms are more impactful and satisfactory to consumers than the judicial. It is equally argued that the judicial mechanisms depict a certain level of risk taking, that is, the risk of winning or losing and hence going without a remedy. This risk factor is much lower in the non or extra â€“ judicial system or mechanism which reveals that in appropriate circumstances, the producers using the good customer relation basis, are minded to compensate even where the consumerâ€™s claim is baseless. In this wise, it is therefore necessary to encourage the utilization of the extra - judicial mechanisms in resolving consumer complaints. Expediency, speed and low cost no doubt support this call.